The annealing effect on thermal diffusivity of polyaniline (emeraldine base) measured using photoflash technique - Liew, Josephine Ying Chyi; Mat Yunus, Wan Mahmood; Abd. Moksin, Mohd Maarof; Grozescu, Ionel Valeriu (Malaysian Solid State Science and Technology Society, 2003)
In this paper, we present the annealing effect on thermal diffusivity of Emeraldine Base−Polyaniline (EB). The thermal diffusivity was measured at room temperature using photoflash technique. The excitation source used consists of a high intensity camera flash. A series of samples annealed at different temperature (25°C, 100°C, 150°C, 200°C, 250°C and 300°C) were investigated and the annealing effect on the thermal diffusivity was discussed in detail. The Scanning Electron Microscopy (SEM) and X−ray Diffraction (XRD) measurement was done to analyze the annealing effect on morphology and sample structure.